Dataset of temperature, heat flux and infrared emission from flat premixed laminar methane-air flames - Tanja Pelzmann; Étienne Robert (Data in Brief, 2022)
To enable the use of flat flame burners in the context of fire resistance testing, we present a data set covering temperature, infrared emission and heat 15 mm above the burner. A laminar premixed methane-air flame is characterized for eleven different fuel/air ratios, ranging from lean (0.9) to rich (1.45), extending an existing a widely used reference [1]. We provide complementing flame temperature readings from thermocouple measurements that can be used for calibration. In addition, broadband flame optical emissions are acquired in the visual (VIS) and the infrared (IR) spectral region. Chemiluminescence measurements reveal the spatial distribution of the OH* radicals. Heat flux density measurements with a water-cooled gauge are also provided. Finally, the expected species concentration, velocity, temperature are obtained from chemical kinetics calculations. Ambient conditions and burner control parameters are presented as supplementary data.